Pendidikan Kesehatan tentang Kebutuhan Gizi Remaja di Pondok Pesantren Al Kinanah Kota Jambi - Dini Junita; Djayusmantoko Djayusmantoko (Jurnal Abdimas Kesehatan (JAK), 2021)
Education on balanced nutrition is still unknown among the wider community, especially teenagers, therefore it is necessary to convey messages of balanced nutrition. The partner chosen in this outreach activity is the Al Kinanah Islamic Boarding School in Jambi City. Al Kinanah Islamic boarding school is one of the Islamic boarding schools in Jambi City. Islamic boarding schools are educational facilities that not only provide religious education, but also general education and independence for students. Students who live in Islamic boarding schools are accustomed to not using communication tools such as cell phones and television like teenagers in general, so that more information is received from the teachers. Efforts to increase knowledge about balanced nutrition in teenagers require a strategic approach to be achieved effectively and efficiently so that it can be applied. One method that can be used is poster and leaflet media. Based on the results obtained from this activity, it is known that the knowledge of the students regarding the guidelines for balanced nutrition is still low. Even though there is an increase, in general the knowledge of students only gets quite good (average score of 65.33). For this reason, it is necessary to carry out health education, especially nutrition in a sustainable manner, if possible it is included in the Islamic boarding school education curriculum. As well as providing health facilities that can be a medium for health information for students through posters or extracurricular organizations at Islamic boarding schools.